1991
DOI: 10.1063/1.460939
|View full text |Cite
|
Sign up to set email alerts
|

The spectroscopic and photophysical effects of the position of methyl substitution. I. 4- and 5-methylpyrimidine

Abstract: Laser-induced fluorescence excitation and dispersed fluorescence spectra of the first n-?r* transition of jet-cooled 2-methylpyrimidine have been recorded and analyzed. This work extends our earlier study of the spectroscopic and photophysical effects of methyl substitution in 4-and 5methylpyrimidine. An unusual Fermi resonance involving the 6~2: progression forms the focus of the present study. The 6~2: vibronic transition is observed to be split into a triad of transitions. Dispersed fluorescence spectra are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In effect, the ground state barrier extends over a relatively wide region, from $5 cm À1 for toluene [8] up to 800 cm À1 in 1-methyl-naphthalene [10]. The corresponding potential barrier for methyl group rotation in the electronically excited systems are as high as 740 cm À1 for 2-methylpyrimidine [14], and decreases down to only 23 and 6 cm À1 in the case of o-fluorotoluene [8] and tolunitrile in the S 1 state [7].…”
Section: Introductionmentioning
confidence: 93%
“…In effect, the ground state barrier extends over a relatively wide region, from $5 cm À1 for toluene [8] up to 800 cm À1 in 1-methyl-naphthalene [10]. The corresponding potential barrier for methyl group rotation in the electronically excited systems are as high as 740 cm À1 for 2-methylpyrimidine [14], and decreases down to only 23 and 6 cm À1 in the case of o-fluorotoluene [8] and tolunitrile in the S 1 state [7].…”
Section: Introductionmentioning
confidence: 93%
“…In methyl groups attached to aromatic rings, several previous studies have shown that the onedimensional potential for internal rotation is often dominated by threefold terms even when only very small asymmetry exists in the positions adjacent to the methylated carbon atom. [35][36][37] The threefold barriers indicate that the methyl group sensitively distinguishes between a methyl hydrogen pointing toward the ring atom on one side versus the other. This same sensitivity may well carry over to the amino group's torsional potential.…”
Section: Discussionmentioning
confidence: 99%
“…The 0-0 transition energy E 0−0 is defined as the difference between the ZPVE-corrected energies: E 0−0 = (E ES + E ES ZPVE ) − (E GS + E GS ZPVE ). In this study, 2-, 4-, and 5-methylpyrimidine (MP) molecules, for which experimental data 69,70 are available, were selected, and CASSCF, NEVPT2, XMS-CASPT2, and some linear-response time-dependent DFT (TD-DFT) 71 with B3LYP, CAM-B3LYP, and LC-BLYP calculations were performed. First, the structures were optimized using the VTZ basis set, and single-point energy calculations were performed using the AVTZ basis set.…”
Section: A Application To Omentioning
confidence: 99%